2008
DOI: 10.1111/j.1469-8986.2008.00750.x
|View full text |Cite
|
Sign up to set email alerts
|

Attentional selectivity for emotional faces: Evidence from human electrophysiology

Abstract: This study investigated the temporal course of attentional biases for threat-related (angry) and positive (happy) facial expressions. Electrophysiological (event-related potential) and behavioral (reaction time [RT]) data were recorded while participants viewed pairs of faces (e.g., angry face paired with neutral face) shown for 500 ms and followed by a probe. Behavioral results indicated that RTs were faster to probes replacing emotional versus neutral faces, consistent with an attentional bias for emotional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
118
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(144 citation statements)
references
References 45 publications
23
118
1
2
Order By: Relevance
“…Some studies manipulating only one of the attention subcomponent have observed effects of emotional attention at the level of the cuelocked N2pc (see Holmes et al, 2009; note however that in their study the emotional cue was presented for 500 ms, which is five times longer than the presentation time of the current study). Other studies found effects of exogenous attention at the level of the target-locked P1 (e.g., Heinze, Luck, Mangun, & Hillyard, 1990).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Some studies manipulating only one of the attention subcomponent have observed effects of emotional attention at the level of the cuelocked N2pc (see Holmes et al, 2009; note however that in their study the emotional cue was presented for 500 ms, which is five times longer than the presentation time of the current study). Other studies found effects of exogenous attention at the level of the target-locked P1 (e.g., Heinze, Luck, Mangun, & Hillyard, 1990).…”
Section: Discussionmentioning
confidence: 93%
“…The N2pc component reflects shifts of spatial attention related to the selection of lateralized stimuli appearing in the left or right visual field. It is elicited at posterior electrodes between 180 and 300 ms after stimulus onset in the hemisphere contralateral to the attended stimulus (Holmes, Bradley, Nielsen, & Mogg, 2009;Luck & Hillyard, 1994;Woodman & Luck, 1999). Once attention has been drawn to a location, it increases the perceptual processing of target stimuli appearing at this location.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason we included measurement of ERPs during task performance. Nevertheless, the demonstration of an attentional bias for threat using RTs would be helpful as a confirmatory measure to strengthen conclusions regarding ERP effects (e.g., Holmes et al, 2009). Inclusion of a larger subject sample is also recommended to increase the statistical power to detect small or medium sized effects.…”
Section: Effects Of Cortisol On Implicit Threat Processingmentioning
confidence: 99%
“…However, these attentional effects have also been demonstrated for positive emotional stimuli (e.g. Holmes, Bradley, Kragh Nielsen, Mogg, 2009;Plichta, Gerdes, Alpers, Harnisch, Brill, 2010). A second way in which emotions may affect cognition is by influencing our evaluations of a situation, person or object.…”
Section: Supporting Evidence For Our Hypothesis -Prior Investigationsmentioning
confidence: 99%